The Size of the Shadow Economies of 145 Countries all over the World : First Results over the Period 1999 to 2003 - Friedrich G. Schneider (Institute for the Study of Labor (IZA), 2004)
Using the DYMIMIC approach, estimates of the shadow economy in 145 developing, transition, developed OECD countries, South Pacific islands and still communist countries are presented. The average size of the shadow economy (in percent of official GDP) over 2002/2003 in developing countries is 39.1%, in transition countries 40.1%, in OECD countries 16.3%, South Pacific islands 33.4% and 4 remaining Communist countries 21.8%. An increasing burden of taxation, high unemployment and low official GDP growth are the driving forces of the shadow economy.
Keywords: H26; H2; H11; D78; O5; O17; 330; shadow economy; tax burden; government regulation; DYMIMIC method; Schattenwirtschaft; Steuerbelastung; Arbeitslosigkeit; Sozialprodukt; Schätzung; Welt